SIMULASI PENGGUNAAN PANEL SURYA ATAP DI LINGKUNGAN KAMPUS POLITEKNIK BATULICIN - Rijal Surya Rahmany; Jefri Aldo; Halim (Scientific Journal of Mechanical Engineering Kinematika, 2023)
The massive use of fossil energy will cause a buildup of CO2 gas from combustion. The Indonesian government is targeting the use of renewable energy as a solution. The renewable energy source that can be chosen is solar energy. However, the use of solar panels requires a plan so that they can operate optimally according to the conditions of the installation area. Therefore, it is necessary to study the use of solar panels on the roofs of buildings as a concrete manifestation of meeting the set targets. In this research, an analysis of electrical energy needs was carried out in Building A of the Batulicin Polytechnic (Polibali), and a simulation of the use of solar panels on the roof of Building A Polibali was conducted to obtain system specifications that could be built. The method used is a direct measurement of electricity usage data in Building A Polibali and a simulation of electrical energy that can be produced from installing solar panels using premium PVSol software. Considering the roof area, 180 solar panel modules were selected with a power rating of 285 W per module and a tilt angle of 15 degrees, so that the simulated system power was 51,3 kWp. The results obtained show that the planned production of electrical energy from solar panels can exceed the overall electricity consumption needs of Building A Polibali, which is 26,512.9 kWh per year, with production from solar panels of 75,217 kWh per year.